The Analysis of Dialogues in the ELT Textbook for Senior High School Students using Leech’s Maxims of Politeness - Septiani, Ella Lovi; Ariyanto, Sugeng; Setyono, Budi (EFL Education Journal, 2023)
This study aimed to analyze the politeness maxims in the government published ELT textbook for Senior High School student. According to Geoffrey Leech's (1983) politeness principle includes six maxims: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. Every maxims has its own purpose so it is necessary for the teacher to understand about each purpose of the maxims. The researcher gathered the dialogues which provide information about maxims of politeness which is represented in the textbook. Textbooks are standard books for instructional purposes which supports the teaching and learning process (Tarigan, 1986: 13). There are some previous researches in using textbook as the instrument. However, mostly the previous researchers are interested in moral value, gender equality, cultural elements and etc. Therefore, in order to explore the use of politeness principle inside a textbook, the researcher interested in conducted a study based on Geoffrey Leech’s six maxims theory in an English Textbook for Senior High School students.